2019
DOI: 10.1016/j.aquaeng.2019.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of peracetic acid on levels of geosmin, 2-methylisoborneol, and their potential producers in a recirculating aquaculture system for rearing rainbow trout (Oncorhynchus mykiss)

Abstract: In recirculating aquaculture systems (RAS)s, off-flavors and odors, mainly caused by geosmin (GSM) and 2-methylisoborneol (MIB), can accumulate in the flesh of fish from RAS water, reducing the profitability of production. In this study, peracetic acid (PAA) was applied in three application intervals to pump sumps of rainbow trout (Oncorhynchus mykiss) reared in RAS. Using a real-time polymerase chain reaction (qPCR), the potential off-flavor producers were quantified using geoA and MIB synthase genes. Strepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…In previous studies, a thick layer of mucus has been observed on fish skin after PAA addition (2.2 mg PAA L −1 1-4 times per week, Lindholm-Lehto et al 2019a). In this study, neither this effect nor any signs of discomfort in fish behavior were observed, which was probably due to the much lower dose of PAA: 15 L PAA d −1 , to inlet water of 32-33 L s −1 (5.2 • 10 −3 -5.4 • 10 −3 L PAA m −3 ), and 4-6 L PAA d −1 to the aeration system of the depuration tanks (1.4 • 10 −3 -2.1 • 10 −3 L PAA m −3 ).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…In previous studies, a thick layer of mucus has been observed on fish skin after PAA addition (2.2 mg PAA L −1 1-4 times per week, Lindholm-Lehto et al 2019a). In this study, neither this effect nor any signs of discomfort in fish behavior were observed, which was probably due to the much lower dose of PAA: 15 L PAA d −1 , to inlet water of 32-33 L s −1 (5.2 • 10 −3 -5.4 • 10 −3 L PAA m −3 ), and 4-6 L PAA d −1 to the aeration system of the depuration tanks (1.4 • 10 −3 -2.1 • 10 −3 L PAA m −3 ).…”
Section: Discussionmentioning
confidence: 91%
“…In particular, Streptomyces, actinomycetes, and myxobacteria are considered to be responsible for GSM and MIB production in RAS (Dickschat et al 2005;Guttman and van Rijn 2008;. In our previous study, Streptomyces was identified as the major GSM producer (Lindholm-Lehto et al 2019a).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, peracetic acid had several limitations and disadvantages. The effectiveness of peracetic acid decreased over time due to peroxide degradation (Lindholm-Lehto et al, 2019;Srivastava et al, 2004). In addition, the by-products of degradation, acetic acid and acetate, encouraged the formation of biofilm which in turn became a protection for opportunistic pathogens (Liu, 2016).…”
Section: Aeromonasmentioning
confidence: 99%